Feasibility of engaging child welfare-involved parents with substance use disorders in research: key challenges and lessons learned. Issue 4 (8th August 2022) - Yoon, Susan; Coxe, Kathryn; Bunger, Alicia; Freisthler, Bridget; Dellor, Elinam; Langaigne, Anika; Millisor, Jennifer
ABSTRACT: Child welfare-involved parents provide an important perspective on service needs and program impact. Similar to other vulnerable and hard-to-reach populations, challenges exist to engaging child welfare-involved parents in community-based research and evaluation. This case study reviews recruitment and data collection strategies for effectively engaging child welfare-involved parents with substance use disorders in a survey to evaluate the Ohio Sobriety, Treatment and Reducing Trauma (START) program – a multi-county initiative implemented to support families involved in the child welfare system due to parental substance use. In this study, child welfare agencies and caseworkers played instrumental intermediary roles to inform eligible parents about research opportunities and facilitate connections with the research team. Ongoing collaboration with child welfare agencies was necessary to establish buy-in for the research, streamline recruitment, and troubleshoot recruitment challenges. Engaging parents directly required strong interpersonal skills, empathy, persistence, attention to detail, and availability during off-business hours. Recruitment strategies also accounted for the unique internet connectivity barriers of parents living in rural communities through survey completion over landline phones, and provisions for cell phone minutes. We offer several recommendations for research methods, budgeting, and staffing when conducting research with child welfare-involved parents with substance use disorders